Climate Risk Management in Agricultural Extension (CRMAE) – Kenya Training Guide - Grossi, Amanda; Dinh, Dannie; Hansen, James; Dinku, Tufa; Murage, Paul; Ruirie, Onesmus; Ngari, Peterson; Okach, Lucas; Kiambe, Kevin; Ngesa, Janet; Mungau, Lilian; Nganga, Irene; et al. (Ministry of Agriculture and Livestock Development, 2025)
This Training Guide is an accompaniment to training materials presented in the Climate Risk Management in Agricultural Extension Reference (CRMAE) Guide and CRMAE Handbook. This Training Guide is intended to be used during implementation of the CRMAE course. This Training Guide was designed to ensure that all of the learning objectives are addressed effectively in the time allotted for each of the four modules that comprise the CRMAE Course. It provides course facilitators with a roadmap and step-by-step instructions for each of the modules and their subcomponents, including each session’s agenda, presentations, activities, and worksheets.